THEORETICAL BASIS OF TEACHING ENGLISH VOCABULARY SKILLS THROUGH SONG VISUALISATION: https://doi.org/10.5281/zenodo.20824381 - Neudakhina , Yulia (Scientific practical conference, 2026)
this article examines the theoretical foundations of teaching vocabulary skills through song visualization. It examines the fundamentals of English language teaching from the perspective of vocabulary skills. It provides an overview of one effective means of teaching vocabulary—the use of musical visualizations, which optimizes all student learning activities. Techniques for using song visualizations in developing vocabulary skills in English are presented.